Pengaruh Luas Lahan, Jumlah Produksi Dan Kurs Dollar Amerika Serikat Terhadap Volume Ekspor Jahe Indonesia Tahun 1993-2012 - Dj, Selvie Yuliana; Wirawan, I Gusti Putu Nata (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
Ginger is a bio pharmacy plant as highest export commodity in biopharmacy category which exported by Indonesia. High-low the ginger export can be influenced by wide of farm, total production, and US dollar rate. This study aims to find out  whether  wide of farm, total production, and US dollar rate simultaneously and partially have effect on volume of ginger export in Indonesia on period of 1993-2012.  in this study export as dependent variable. Wide of farm, total production, and US dollar rate as independent variable. Data collection method by using documentation method. Data analysis technique by using multiple linear regression. The result showed wide of farm, total production, and US dollar rate simultaneously have significant toward volume of ginger export in Indonesia on period of 1993-2012. value of R 2 = 0,988 its mean 98,8 percent the wide of farm, total production, and US dollar rate have effect on volume of ginger export in Indonesia. Wide of farm, total production and US dollar rate partially have positive effect on volume of ginger export in Indonesia on period of 1993-2012.
Keywords: Luas lahan, Jumlah produksi, kurs dollar AS, Volume ekspor, Jahe